Minimizing maximum tardiness in single FMS machine scheduling with tool changes - Lin, Kai-Yung; Chung, Yu-Ko (Journal of information & optimization sciences, 2009)
Flexible Manufacturing System (FMS) is a programmable automation system that efficiently accommodates product variations and small-lot production capability. Tool change is an important issue for FMS tool management. Previous literature on tool management addresses this issue, but assumes that the change is due only to part mix. In practice, however, most tool changes are the result of tool wear. This study considers the problem of scheduling a set of jobs on a single FMS where the cutting tool is subject to wear, aiming to minimize the maximum tardiness. Two mixed binary integer programming models were developed to solve this problem optimally. We developed the heuristic method to compute result to demonstrate the efficiency of the models.